Improving Students Writing Descriptive Skills Through Snowball Throwing Games Technique at SMK Immanuel Medan - Aprilia, Sarah; Aritonang, Romaito; Asrul, Nurmahyuni; Yunanda, Fachri; Amaniarsih, Dwi Suci (Pusdikra Publishing, 2025)
The Snowball Throwing Games method has proven effective in enhancing students' descriptive writing skills. Beyond measurable improvements in academic performance, this interactive and collaborative approach increased student motivation and fostered a more engaging classroom atmosphere. The method encouraged active participation, creativity, and self-expression, helping students build confidence and develop their writing abilities. Moreover, the method significantly improved students’ social interaction and teamwork, which positively influenced their ability to collaborate during writing tasks. Particularly in writing classes often perceived as challenging, the dynamic and supportive environment reduced student anxiety and minimized the fear of making mistakes. Each phase of implementation was strategically designed to facilitate classroom communication and highlight various aspects of the Snowball Throwing Games technique. These included student engagement, behavioral change, the development of critical thinking skills, and the integration of digital tools to support learning goals. The findings indicate that this method is both practical and effective in improving writing proficiency while fostering a positive and collaborative learning environment.